(untitled) (Torani Journal of Fisheries and Marine Science, 2016)
The vulnerability of Makassar coast was measured using parameters of Coastal Vulnerability Index (CVI). CVI value was determined using geomorphology, shoreline change, coastal slope, mean wave height, mean tidal range, and relative sea level change parameters. The Makassar coast was divided into a numbers of cells, each with the length of 1 km and width of 0.5 kminto the sea. CVI values werecalculated for each cell and the coastal vulnerability wereclassifiedinto five categories: very low - low - medium - high - very high. The results show that the coastline with high to very high vulnerability index are located at the southern part of Makassar, while the northern coastline generally have low to moderate vulnerability. The CVI parameters which contributed to high susceptibilitywere the coastal slope and the shoreline change parameters. Keywords: Coastal Vulnerability Index, coastal slope and shoreline change, Makassar.